MANAJEMEN PENDIDIKAN INKLUSIF PADA SEKOLAH MENENGAH KEJURUAN - Nurcahyarini, Femilia (Jurnal Pendidikan Khusus, 2017)
ABSTRACT:Inclusive education is defined as the incorporation of special education and regular education within a unified education system. Through inclusive education of students with special needs can be socialized and integrated with other learners peers in regular schools. Then in order to obtain the success of inclusive educational goals required a good management system and organized. The purpose of this study was to describe the management of inclusive education in SMKN 8 Surabaya. This research uses descriptive method with qualitative approach. Data collection techniques obtained through interview, observation and documentation. In the data analysis techniques used include condensation steps, data presentation, and conclusion and verification. The conclusion of this study were: 1) the management of learners in receipt of learners with special needs in all types of disabilities but still consider his ability as well as the identification and assessment to determine the initial ability of learners with special needs, 2) management of curriculum on inclusive education using the Curriculum 2013 modified, 3) management of teachers and do not have to have any special requirements in dealing with learners with special needs, 4) management classes and learning to use the form of regular classes full and pull out on certain days only, 5) management of facilities and infrastructure has not yet held a study related to the procurement of equipment and media for learners with special needs, 6) management of funding coming from the government, parents and the community, 7) management of community relations with the school established by the stakeholders who participated.   Keywords: management, inclusive education, learners with special needs